Comparison of Hereford steers sired by small, medium and large size bulls. - Smith, E.F.; Mackintosh, D.L.; Weber, A.D. (Kansas Agricultural Experiment Station, 2012)
The project involves comparisons of steer calves sired by small, medium, and large size bulls at each of the three stations under three standard systems of feeding and management. System I, immediate full feeding for 225 days. System II, a deferred full feeding program in which the steer calves are wintering well, grazed without grain from May 1 to August 1, and then full fed in dry lot 160 days. System III, has for its objective the production of two-year-old grass fat steers without the feeding of grain. Phases under this system include: wintering as calves without grain grazing as yearlings a full season without supplemental feed; wintering as yearlings without grain; grazing as two-year-olds without supplemental feed and selling as slaughter cattle directly off pasture.
Keywords: Beef; Performance; Size